Identifying a therapeutic target for vancomycin against staphylococci in young infants. (17th January 2022) - Gwee, Amanda; Duffull, Stephen B.; Daley, Andrew J.; Lim, Michelle; Germano, Susie; Bilal, Hajira; Hall, Samantha; Curtis, Nigel; Zhu, Xiao
Abstract: Objectives: To determine the therapeutic target of vancomycin in young infants with staphylococcal infections. Methods: Retrospective data were collected for infants aged 0 to 90 days with CoNS or MRSA bacteraemia over a 4 year period at the Royal Children's Hospital Melbourne, Australia. Vancomycin broth microdilution MICs were determined. A published pharmacokinetic model was externally validated using the study dataset and a time-to-event (TTE) pharmacodynamic model developed to link the AUC of vancomycin with the event being the first negative blood culture. Simulations were performed to determine the trough vancomycin concentration that correlates with a 90% PTA of the target AUC24 . Results: Thirty infants, 28 with CoNS and 2 with MRSA bacteraemia, who had 165 vancomycin concentrations determined were included. The vancomycin broth microdilution MIC was determined for 24 CoNS and 1 MRSA isolate, both with a median MIC of 1 mg/L (CoNS range = 0.5–4.0). An AUC0–24 target of ≥300 mg/L·h or AUC24–48 of ≥424 mg/L·h. increased the chance of bacteriological cure by 7.8- and 7.3-fold, respectively. However, AUC0–24 performed best in the pharmacokinetic-pharmacodynamic model. This correlates with 24 to 48 h trough concentrations of >15–18 mg/L and >10–15 mg/L for 6- and 12-hourly dosing, respectively, and can be used to guide vancomycin therapy in this population. Conclusions: An AUC0–24 ≥300 mg/L·h or AUC24–48 ≥424 mg/L·h was associated with an increase in bacteriological cure in young infants with staphylococcal bloodstream infections.